PENGARUH PROMOSI, PERSEPSI MANFAAT DAN GAYA HIDUP TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET - Saragih, Hari Setiawan; Soemitra, Andri; Nurbaiti, Nurbaiti (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Technology is now a major component since it is becoming easier for customers to use non-cash payment methods due to its rapid development. With the use of e-wallets, the digital economy now prioritizes the needs and lifestyles of its users due to the influence of technical advancements. The purpose of this study is to ascertain and examine how marketing, advantages perceptions, and lifestyle choices affect female students' decisions to use e-wallets in Medan. Quantitative research is used in this research strategy. The major data used in this study came from questionnaires. There were one hundred female students in the city of Medan who made up the sample for this study. The decision to use an e-wallet is the dependent variable in this study variable. The independent variables include promotion, perceived benefits, and lifestyle. Multiple linear regression analysis is the method of analysis. The F test, t test, and coefficient of determination test are used in hypothesis testing. The study's findings demonstrate that the decision to use an e-wallet concurrently is positively and significantly influenced by promotion, perceived benefits, and lifestyle. Some study findings indicate that among female students in the city of Medan, promotions, perceived benefits, and lifestyle have a big impact on whether or not they decide to use an e-wallet.